Taking Time - Harry, C.C. (SpringerBrief. Philos., 2015)
Despite the language we saw in the previous chapter, which allowed for time apprehension by perception and marking, in Physics iv 14, Aristotle famously argues that time is dependent on nous. © 2015, The Author(s).
Journal Abbreviation: SpringerBrief. Philos.
Keywords: Human Child; Nonhuman Animal; Pure Actuality; Sense Perception; Time Perception; dept.phi